2017
DOI: 10.3389/fmicb.2017.01314
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral Properties of the Natural Polyphenols Delphinidin and Epigallocatechin Gallate against the Flaviviruses West Nile Virus, Zika Virus, and Dengue Virus

Abstract: The Flavivirus genus contains important pathogens, such as West Nile virus (WNV), Zika virus (ZIKV), and Dengue virus (DENV), which are enveloped plus-strand RNA viruses transmitted by mosquitoes and constitute a worrisome threat to global human and animal health. Currently no licensed drugs against them are available, being, thus, still necessary the search for effective antiviral molecules. In this line, a novel antiviral approach (economical, simple to use, and environmental friendly) is the use of natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
144
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(148 citation statements)
references
References 37 publications
4
144
0
Order By: Relevance
“…However, no or minimal inhibition was observed with other flavivirus, including JEV, YFV, and ZIKV, contradicting previous reports by Carneiro [20] and Vázquz-Calvo [23]. In those reports, ZIKV particles were incubated with EGCG for 1 h before the mixture was applied to cells.…”
Section: Antiviral Activity Of Catechins On Enveloped (+) Ssrna VImentioning
confidence: 68%
See 2 more Smart Citations
“…However, no or minimal inhibition was observed with other flavivirus, including JEV, YFV, and ZIKV, contradicting previous reports by Carneiro [20] and Vázquz-Calvo [23]. In those reports, ZIKV particles were incubated with EGCG for 1 h before the mixture was applied to cells.…”
Section: Antiviral Activity Of Catechins On Enveloped (+) Ssrna VImentioning
confidence: 68%
“…That the same year, Vázquz-Calvo et al [23] assayed the effect of a series of polyphenols on WNV-NY99 infection and found that delphinidin ( 14 ) and EGCG ( 1 ) reduced the viral titer by more than three orders of magnitude as the virus pretreated with 10 μM of each polyphenol. These compounds mainly affected the attachment and entry steps of the virus life cycle.…”
Section: Antiviral Activity Of Catechins On Enveloped (+) Ssrna VImentioning
confidence: 99%
See 1 more Smart Citation
“…The crystal structures of all these proteins have been already resolved and will certainly help to find new antivirals [22][23][24][25][26][27][28][29][30]. In the same way, structures from other viral proteins are also available that could help to design ZIKV therapeutic alternatives, such as those of the capsid C protein [31], which destabilization may impair ZIKV multiplication, the NS1 [32,33], an immunomodulator, or the envelope glycoprotein [34][35][36], which mediates cell binding and endosomal fusion, constitutes a major target for neutralizing antibodies, and could be also the target for virucidal compounds [37].…”
Section: Direct-acting Antiviralsmentioning
confidence: 99%
“…Even more, compounds present in many natural products that also target the viral particle, such as the polyphenols epigallocatechin gallate and delphinidin chloride, also exhibit anti-ZIKV activity, probably through a virucidal effect Vázquez-Calvo et al, 2017b).…”
Section: Antiviralsmentioning
confidence: 99%